2019
DOI: 10.1175/jamc-d-18-0164.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Wind Data from Reanalyses for the Upper Midwest

Abstract: Wind is an important atmospheric variable that is receiving increased attention as the world seeks to shift from carbon-based fuels in order to mitigate climate change. This has resulted in increased need for more temporally and spatially continuous wind information, which is often met through the use of reanalysis data. However, limited work has been done to assess the long-term accuracy of the wind data against observations in the context of specific applications. This study focuses on the representation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…The piecewise trends show wind speed trends calculated by reanalysis data have been significantly underestimated compared to the observed piecewise trends in most regions. This is consistent with the results obtained by Coburn (2019). JRA-55 can capture the phenomenon of global terrestrial stilling well, especially the stilling in Europe, North America, and Africa.…”
Section: A Inconsistent Wind Speed Trends Between Reanalysis and Observationssupporting
confidence: 92%
“…The piecewise trends show wind speed trends calculated by reanalysis data have been significantly underestimated compared to the observed piecewise trends in most regions. This is consistent with the results obtained by Coburn (2019). JRA-55 can capture the phenomenon of global terrestrial stilling well, especially the stilling in Europe, North America, and Africa.…”
Section: A Inconsistent Wind Speed Trends Between Reanalysis and Observationssupporting
confidence: 92%
“…These results are in accordance with other studies (Decker et al ., 2012; Cannon et al ., 2015; Kaiser‐Weiss et al ., 2015; Rose and Apt, 2016; Minola et al ., 2020), where wind speeds from different reanalyses products are compared against flux tower or meteorological data in different areas of the globe. But in contrast with others (Toledo et al ., 2015; Coburn, 2019), probably mainly related to the studied area. Coburn (2019) in the upper Midwest of the United States, showed that correlations between reanalyses and observations improve with higher temporal reanalysis resolution (monthly correlations are smaller than daily correlations).…”
Section: Resultsmentioning
confidence: 97%
“…But in contrast with others (Toledo et al ., 2015; Coburn, 2019), probably mainly related to the studied area. Coburn (2019) in the upper Midwest of the United States, showed that correlations between reanalyses and observations improve with higher temporal reanalysis resolution (monthly correlations are smaller than daily correlations). Note that all these previous studies have a more limited studied area compared to the work presented here, in which the whole European area is analysed and so it would include all those different and mixed regional behaviours.…”
Section: Resultsmentioning
confidence: 97%
“…We characterized daily synoptic patterns over the Eolos site using a series of experiments to find the optimal synoptic classification for the site. We tested two clustering algorithms (K‐means, a nonheirarchical clustering method 22 and self‐organizing maps [SOM], a neural network‐based classification method 23,24 ), two reanalysis datasets as input for the clustering algorithm (ERA5 25 and MERRA‐2, 26 based in part on research by Coburn 27 ), and different numbers of clusters (i.e., synoptic types) for grouping the data (5, 10, 15, 20, and 25). We also tested different clustering variables (sea level pressure [SLP], which is commonly used for synoptic classification, 2‐m air temperature [T2m], which was used to potentially capture thermodynamic effects, or both in conjunction) and the spatial range over which to perform the classification (1000 × 1000, 2000 × 2000, and 3300 × 3300 km 2 or roughly 9° × 9°, 18° × 18°, and 27° × 27° latitude and longitude at 45°N).…”
Section: Methodsmentioning
confidence: 99%
“…Coburn 27 ), and different numbers of clusters (i.e., synoptic types) for grouping the data (5, 10, 15, 20, and 25). We also tested different clustering variables (sea level pressure [SLP], which is commonly used for synoptic classification, 2-m air temperature [T2m], which was used to potentially capture thermodynamic effects, or both in conjunction) and the spatial range over which to perform the classification (1000 Â 1000, 2000 Â 2000, and 3300 Â 3300 km 2 or roughly 9 Â 9 , 18 Â 18 , and 27 Â 27 latitude and longitude at 45 N).…”
Section: Synoptic Classificationmentioning
confidence: 99%